PEMANFAATAN SIKLUS PEMBUANGAN AIR TERHADAP SISTEM DRAINASE PERUMAHAN KOTA - Azwarman Azwarman (Jurnal Civronlit Unbari, 2018)
Flooding as one of the big problems in Jambi City can be overcome by arranging drainage and drainage system for flood control. However, excess water during floods and used in anticipation of water shortages during the dry season has not been widely studied. The basic principle of water utilization is the engineering into a system of absorption wells or also known as water conservation which aims to prevent or minimize the lost water as the flow of the surface and store it as much as possible into the earth. The study was conducted in Jambi City, taking a case study of housing by conducting engineering to the housing drainage system so that new designs are emerging. The analysis is in the form of field observation and data analysis. This residential location is located in Paalmerah Village with 78/105 building type and there are 23 units of buildings with garden facilities and security. The results show that based on the intensity of rainfall, the dimensions of absorption wells and reservoirs can be determined for Jatayu housing. The dimension of absorption well is with the diameter of circle 1m and height 1.89 m while for the storage tub dimension is rectangular cross section with size 2m x 1.5 m x 1.5 m.Keywords: rainfall, water conservation, efficiency